Epidemiological analysis of reported cases of congenital syphilis in a city in the interior of Bahia (Research, Society and Development, 2024)
Introduction: The pregnant woman with syphilis when umtreated or offered an inadequate therapeutic plan increases the susceptibility of the baby to contact T. Pallidum, thus developing congenital syphilis (CS). Objectives: To identify the epidemiological profile of CS in a city in the interior of Bahia from 2017 to 2021; Detect the percentage of pregnant women affected by syphilis who underwent prenatal care, according to the cs notification form in a city in the interior of Bahia in 2017 to 2021; To highlight the moment of the diagnosis of maternal syphilis and the inclusion of the partner in the therapeutic plan in a city in the interior of Bahia in 2017 to 2021; To identify the age group, gender, evolution and clinical classification of neonates and infants reported with CS in a city in the interior of Bahia from 2017 to 2021. Methodology: Descriptive, exploratory and quantitative study, based on the information provided by SINAN, regarding the cases of CS that occurred in a municipality in the interior of Bahia in the year 2017 to 2021. Results: 208 children were investigated, and there was a marked predominance of sexual partnership excluded from therapy, with 142 (68.27%) individuals. A majority percentage of detection is demonstrated until 6 days of life, with 196 (94.23%) and 144 (83.24%) remained alive until the period of notification and investigation. Final considerations: There was a marked percentage of diagnosis in children with CS at an opportune time and with a favorable clinical outcome.